(untitled) (Journal of Teleological Science, 2026)
This article proposes a reading of Aristotle as the antecedent from which the capacity to express the just [to dikaion] and the unjust [to adikon] marks the threshold where political experience intertwines with the ethical and juridical dimensions. Through three layers of analysis – just-justice in the ethical field, just-adjusted in the judicative-normative sphere, and just-rightness in the political domain – it seeks to demonstrate how Aristotelian practical philosophy articulates prudence [phronesis], equity [epieikeia], and artisanal skill [kheirotekhne] in the configuration of a justice that harmonizes the ethical, juridical, and political spheres, with the just as proportional, mediational, and equitable rightness as its gravitational center.